Comparing of innovative and traditional technologies of wood houses for using the efficiency index - Å vajlenka, Jozef; Kozlovská, Mária (International Journal of Engineering and Technology, 2018)
Sustainable development is a term, which came in at present in many spheres economic and social life. Many of the development and growth dimensions that have been evaluated so far have recently been complemented by the sphere of sustainability. In the context of sustainable construction, there is a host of other environmental, social and economic criteria which show the extent to which a construction and its use affects its users' health, or even the health of the whole society. The aim of this paper is to present a comparing of innovative and traditional technologies of wood houses for using the efficiency index. Based on a comparison of generally defined formulations of efficiency, it was created through the authors of this manuscript the formula for efficiency evaluation, determining efficiency as a ratio of synthetic to analytic efficiency indicators. By comparative analysis we found that the panel construction system, representing off-site technologies, is considerably more efficient when compared with instances of traditional on-site technologies.